'The notorious gambling class': patterns of gambling among young people in Denmark. (16th March 2017) - Kristiansen, Søren; Reith, Gerda; Trabjerg, Camilla Maria
ABSTRACT: In this study, using a three wave qualitative longitudinal data set, we explored patterns of change in gambling behavior among a sample of young Danes. A total of 48 informants participated in all three sweeps of interviews. The overall aim was to explore the complexities and social contexts, as well as the subjective meanings that underlie gambling behavior changes. We identified four different types of gambling pathways, each illustrating different types of movement over time: intensification; reduction; stability, and those that were non-linear. Our overall finding was that transitions or oscillations in behavior are more common than a progressive linear gambling pattern, and that these changes are affected by a number of contextual factors. The implications for further research and policy are discussed.